2020
DOI: 10.1371/journal.pone.0234565
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor -173 G>C single nucleotide polymorphism and its association with active pulmonary tuberculosis

Abstract: The establishment of candidate genes associated with susceptibility to TB is a challenge especially due to divergent frequencies among different populations. The objective of this study was to evaluate the association between macrophage migration inhibitory factor (MIF)-173 G>C single nucleotide polymorphism (SNP) and susceptibility to pulmonary TB in a population of southern Brazil. Methods Case-control study. Patients > 18 years old, diagnosed with pulmonary TB were included. The control group consisted of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Several studies have reported that the C allele of MIF -173 G/C (rs755622) was linked to TB in Colombia, South Africa, and the East China population [19], [20], [41], [42]. However, this study did not found an association between the genotype of MIF -173 G/C with the risk of pulmonary TB, and this result was similar to a study in the Brazilian population [18]. The diversity in different ethnicities or populations and diverse clinical features may contribute to the genotype distribution of VDR and MIF polymorphisms and different results explaining this correlation to TB.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Several studies have reported that the C allele of MIF -173 G/C (rs755622) was linked to TB in Colombia, South Africa, and the East China population [19], [20], [41], [42]. However, this study did not found an association between the genotype of MIF -173 G/C with the risk of pulmonary TB, and this result was similar to a study in the Brazilian population [18]. The diversity in different ethnicities or populations and diverse clinical features may contribute to the genotype distribution of VDR and MIF polymorphisms and different results explaining this correlation to TB.…”
Section: Discussionsupporting
confidence: 83%
“…Besides that, the data analysis regarding the haplotype is still limited [16]. Likewise, for the MIF -173 G/C SNP (rs755622), existing studies linking it to the risk of TB have shown varying results [18], [19], [20]. Thus, more studies are needed to confirm the association of these polymorphisms to TB risk.…”
Section: Introductionmentioning
confidence: 99%
“…(32,33) However, in a more recent study, found no association between MIF-173 G/C and susceptibility to TB. (34) In an in vitro study using human THP-1 macrophages (cells used as a model for human monocytes), MIF was released rapidly from human macrophages once stimulated by mycobacteria and was fairly stable within 1 hour and then increased after four and six hours, as well as with MIF transcription also upregulated. (15) This result indicated that in acute mycobacterial infection the MIF will predominant to reduce the infection process.…”
Section: Discussionmentioning
confidence: 99%